Repair of bone defects in rhesus monkeys with α1,3-galactosyltransferase-knockout pig cancellous bone - Wang, Wenhao; Lu, Jiansen; Song, Ying; Zeng, Chun; Wang, Yongkui; Yang, Cheng; Huang, Bin; Dai, Yifan; Yang, Jian; Lai, Liangxue; Wang, Liping; Cai, Daozhang; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Since xenografts offer a wide range of incomparable advantages, they can be a better option than allografts but only if the possibility of immunological rejection can be eliminated. In this study, we investigated the ability of α1,3-galactosyltransferase (α1,3-GT) gene knockout (GTKO) pig cancellous bone to promote the repair of a femoral condyle bone defect and its influence on heterologous immune rejection. Cylindrical bone defects created in a rhesus monkey model were transplanted with GTKO bone, WT bone or left empty. For immunological evaluation, T lymphocyte subsets CD4+ and CD8+ in peripheral blood were assayed by flow cytometry, and the IL-2 and IFN-γ contents of peripheral blood serum were analyzed by ELISA at 2, 5, 7, 10 and 14 days post-surgery. Micro-CT scans and histological assessment were conducted at 4 and 8 weeks after implantation. Compared with WT-pig bone, the heterologous immunogenicity of GTKO-pig bone was reduced. The defect filled with fresh GTKO-pig bone was tightly integrated with the graft. Histological analysis showed that GTKO-pig cancellous bone showed better osseointegration and an appropriate rate of resorption. Osteoblast phenotype progression in the GTKO group was not affected, which revealed that GTKO-pig bone could not only fill and maintain the bone defect, but also promote new bone formation.